The influence of film attractiveness and electronic word of mouth, towards intention to visit sumba: a case study of Susah Sinyal movie (Research, Society and Development, 2020)
The film's capabilities segment various social classes, realizing the experts whose films have the potential to affect the audience of its connoisseurs. The ability of film which could penetrate various social class segment, realizing the experts about film as part of mass media, could influence their audiences by spreading the hidden message. This study aims to determine if film attractiveness and electronic word of mouth are factors which can influence visit intention and decision to Sumba in Susah Sinyal movie. This research uses online questionnaire with purposive sampling technique that distributed to 150 respondents who have watched Susah Sinyal movie and have visited Sumba. After the data is analysed using multiple regression models with SPSS program, the result shows that film attractiveness have an influence on visit intention while electronic word of has no influence on visit intention. It concluded that there is an influence between the attractiveness of the film towardsvisit intention.